An Efficient Geometric Parametrization Technique for the Continuation Power Flow through the Tangent Predictor - Bonini Neto, A.; Alves, D.A. (Trends in Computational and Applied Mathematics, 2008)
This paper presents a new parameterization scheme to the continuation power flow that allows the complete tracing of P-V curves and the computation of the maximum loading point of power system, without ill-conditioning problems of the Jacobian matrix and without the exchange of parameter. The objective is to present the technique in a clear and didactic way.